REST AREA JALAN TOL SOLO – SEMARANG MELALUI ASPEK ESTETIKA IDIOMATIK KOTA UNGARAN - Lina Nida’ul Lathifah; Muhammad Asrori; Titis Srimuda Pitana (Universitas Sebelas Maret Surakarta, 2014)
Abstract: Rest Area of Solo – Semarang Toll Road in the manner of idiomatic aesthetic aspect of Ungaran City is a side-road public space which provides resting facilities for road user to regain their fitness, and also for location signing through identity emergence. For those purposes, there are several design problems to be resolved, (1) How the space programming concept of the rest area could optimally regain the user’s fitness through building design, (2) How the building appearance concept could give information about location and identity of Ungaran City itself. The design strategy for the rest area is regaining user’s fitness by emphasizing psychological and behavioral aspect which affect the space programming of the rest area design which is focusing in facilities provision based on the psychoanalysis and circulation arrangement based on the place-centered mapping theory. Ungaran City location signing could be implemented by using the idiomatic aesthetic aspect of Kitsch, which put Gedongsongo Temple as observation object and city identity in the shape of element function diversion, object transformation as well as object veneration. Keywords: Gedongsongo Temple, Kitsch Idiomatic Aesthetic Aspect, Psychoanalysis, Rest Area